If frogs made weather - Bauer, Marion Dane.; Donohue, Dorothy (New York : Holiday House, 2005)
A young child ruminates on the favorite weather of ten different animals.
Keywords: Animals -- Juvenile fiction; Animals -- Fiction; Weather -- Fiction